2017
DOI: 10.1590/0370-44672017700022
|View full text |Cite
|
Sign up to set email alerts
|

Punching of reinforced concrete flat slabs with holes and shear reinforcement

Abstract: Punching shear is a possible type of failure that occurs in reinforced concrete flat slabs, which can develop with an ultimate load below flexural capacity. Several researchers have studied the punching resistance of flat slabs over recent years. Although they have made great advances, there are codes that show different approaches to a singular design. Some codes show that there exist contradictions, even in the simplest situations, such as concentric loads. Most codes prescribe empirical expressions based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…According to Trautwein (2011), a punching shear failure may lead to progressive collapse if the structure does not have enough load redistribution capacity. Several variables influence punching shear in flat slab design such as the use of high strength concrete, column geometry at the slab interface, slab depth and use of reinforcement to improve shear strength as shown in previous research done by Gomes and Regan (1999), Borges, Melo and Gomes (2013) and Silva et al (2017). According to Maghsoudi and Sharifi (2009), self-compacting concrete (SSC) improves the punching shear strength of slabs although they present less ductility then conventional concrete and a smoother failure surface thus decreasing the contribution of aggregate interlock.…”
Section: Introductionmentioning
confidence: 92%
“…According to Trautwein (2011), a punching shear failure may lead to progressive collapse if the structure does not have enough load redistribution capacity. Several variables influence punching shear in flat slab design such as the use of high strength concrete, column geometry at the slab interface, slab depth and use of reinforcement to improve shear strength as shown in previous research done by Gomes and Regan (1999), Borges, Melo and Gomes (2013) and Silva et al (2017). According to Maghsoudi and Sharifi (2009), self-compacting concrete (SSC) improves the punching shear strength of slabs although they present less ductility then conventional concrete and a smoother failure surface thus decreasing the contribution of aggregate interlock.…”
Section: Introductionmentioning
confidence: 92%
“…Likewise, the capacity ratios calculated with the nonlinear punching circumference ratio equation proposed in Eq. (25), which is proposed within the scope of this study, are given in Table 7. It is seen that the proposed equation for circular openings, in which the suggested results in Table 7 are examined, does not give as successful results as for slabs with square openings.…”
Section: Proposed Equationmentioning
confidence: 99%
“…It was stated that the results were in good agreement with the finite element analysis results. After a detailed literature review to determine the maximum punching bearing strength values of opening two-way reinforced concrete slabs within the scope of the study, Živković et al [5]; Pinto et al [6]; Augustin et al [7]; Lourenço et al [8]; Bompa and Onet [19]; Oukaili and Salman [20]; Durucan and Anil [21]; Ha et al [22]; Ilbegyan et al [23]; Abduljaleel et al [24]; Silva et al [25]; Balomenos et al [26]; Liberati et al [27]; Kormosova et al [28] have been found. After a comprehensive literature review, the limited number of studies listed above were found, examining the effects of openings on the maximum bearing capacity of two-way reinforced concrete slabs under punching loading.…”
Section: Introductionmentioning
confidence: 99%
“…ACI 318-19 [18] provisions were used to calculate the shear and flexural strengths of specimens. Shear strength provided by concrete is calculated using Equation (1).…”
Section: Specimen Designmentioning
confidence: 99%
“…Nowadays, flat slabs are widely used because of their simple reinforcement details, reduced building heights, rapid construction etc. A flat slab without beams is less rigid and open to larger vertical displacements than conventional slabs [1,2]. Flat slabs are prone to punching shear due to the accumulation of high shear stresses in the vicinity of slab-column junction [3,4].…”
Section: Introductionmentioning
confidence: 99%